Analisis Faktor-Faktor Yang Berhubungan Dengan Length Of Stay (Los) Pasien Di Instalasi Gawat Darurat Uobk Rumah Sakit Paru - Putri Gaudy; Suhat; Budiman (LPPM ITEKES Mahardika, 2026)
Length Of Stay (LOS) is an important indicator of the effectiveness and efficiency of Emergency Department (ED) services and ideally should not exceed 4 hours, considering the critical role of the ED in managing emergency cases. This study aims to analyze the most dominant factors associated with LOS in the ED of UOBK West Java Provincial Pulmonary Hospital. This study employed an analytic observational design with a cross-sectional approach involving 125 ED patients during the period of December 21–31, 2025, using a total sampling technique. Data were collected through observation sheets and medical records, and analyzed using Chi-Square tests and binary logistic regressio. The results showed significant associations between age (p = 0.024), time of arrival (p = 0.036), level of acuity (p = 0.0001), and final service disposition (p = 0.0001) with LOS. No significant associations were found for gender (p = 0.596), education level (p = 0.368), employment status (p = 1.000), diagnosis (p = 0.461), and payment status (p = 0.692). Binary logistic regression analysis identified final service disposition (OR = 11.198; p = 0.0001) and time of arrival (OR = 2.834; p = 0.027) as the most dominant factors influencing LOS in the ED. Final service disposition and time of arrival were the most dominant factors affecting LOS in the ED of UOBK West Java Provincial Pulmonary Hospital. Therefore, optimization of resource allocation to accelerate service delivery, reduce overcrowding, and improve the quality and safety of patient care.